Hubungan Antara Social Support Terhadap Employee Experience Pada Karyawan Depo Pt. X (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the significant relationship between Social Support and Employee Experience among employees at the Depot of PT. X. The background of this study is the strategic transformation of PT X from a manual mechanical operational system to a modern, digital, and automated one, which aims to increase efficiency and competitiveness. This change creates significant adaptation challenges for employees, especially those accustomed to old work patterns, which causes difficulties, anxiety, and the need for new skills. Nevertheless, the results of initial observations and interviews indicate that employees are able to respond quickly and demonstrate a positive Employee Experience, reflected in the existence of autonomy in decision-making, self-confidence (competence) in completing tasks, and supportive working relationships (relatedness). The established social support includes emotional, informational, instrumental, and appraisal assistance, which are crucial in helping employees adapt to new tools. This study uses a quantitative correlational method. The study population is the employees of the Depot of PT X.. Data collection was carried out using the Employee Experience and Social Support scales. It is hoped that the results of this study will prove the hypothesis of a positive relationship between the two variables, while also providing practical contributions to companies in building an adaptive work culture by strengthening social support amidst technological innovation.